Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/ana.26654
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Detected before or after Stroke: Role of Anticoagulation

Abstract: BackgroundAtrial fibrillation (AF) known before ischemic stroke (KAF) has been postulated to be an independent category with a recurrence risk higher than that of AF detected after stroke (AFDAS). However, it is unknown whether this risk difference is confounded by pre‐existing anticoagulation, which is most common in KAF and also indicates a high ischemic stroke recurrence risk.MethodsIndividual patient data analysis from 5 prospective cohorts of anticoagulated patients following AF‐associated ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…A recent combined cohort study including the cohort of SAMURAI-NVAF showed that no significant difference was observed between patients with AFDAS, which was defined in the same way as in the present study, and KAF regarding the risk of recurrent ischemic stroke. 20 However, patients with AFDAS had a lower risk of embolic events than those with KAF in the present study. This discrepancy might be explained by the fact that the prevalence of sustained AF in patients with AFDAS in the present study was lower than that in the combined cohort study (36.3% vs 64.6%).…”
Section: Discussioncontrasting
confidence: 58%
“…A recent combined cohort study including the cohort of SAMURAI-NVAF showed that no significant difference was observed between patients with AFDAS, which was defined in the same way as in the present study, and KAF regarding the risk of recurrent ischemic stroke. 20 However, patients with AFDAS had a lower risk of embolic events than those with KAF in the present study. This discrepancy might be explained by the fact that the prevalence of sustained AF in patients with AFDAS in the present study was lower than that in the combined cohort study (36.3% vs 64.6%).…”
Section: Discussioncontrasting
confidence: 58%
“…It raises the possibility that the difference in risk may be influenced by pre-existing anticoagulation, which is more common in KAF and signifies a heightened risk of ischemic stroke recurrence [72]. A recent study by Lyrer et al [73] challenged the idea that KAF and AFDAS are distinct prognostic entities and suggest that, rather than solely attributing a high stroke recurrence risk to KAF, future research should concentrate on understanding the causes of stroke in patients despite anticoagulation treatment to develop more effective preventive measures.…”
Section: Treatment Of Atrial Fibrillationmentioning
confidence: 99%
“…Although this study 6 is important, it has several limitations worth noting. Authors lack data on AF burden, which is known to be associated with ischemic stroke risk in AF.…”
mentioning
confidence: 99%
“…In a study published in this issue of Annals of Neurology , Lyrer et al 6 analyzed data from a multicenter study of patients with acute ischemic stroke in the setting of AF. They evaluated the risk of recurrent stroke in patients with AF, comparing those with two different categories of AF detection: AFDAS versus those with Known AF.…”
mentioning
confidence: 99%
See 1 more Smart Citation